Vektor Kendali Permainan Dinamis LQ Non-Kooperatif Waktu Tak Berhingga - Nilwan Andiraja (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2016)
In this paper discuss about control vector with Nash criterion in linier quadratic non-cooperativedynamic game two player case with infinite time. Discuss was started from general equations for noncooperative dynamic game N player for infinite time with several assumption. Then, with same assumptionto made general equation for non-cooperative dynamic game two player for infinite time. Based ondifferential equation and objective function for each player algebraic Riccati equation was formed for firstplayer and second player, to made control vector with Nash criterion. Finally, control vector with Nash forfirst player and second player used to analysis about stability of dynamic function.Keywords: game, linear, quadratic, non-cooperative, control